Initial Experience With the Pediatric Impella Device: A Feasibility Study in a Porcine Model. Issue 4 (24th May 2016) - Webb, Melissa K.; Wang, Jian; Riegel, Matthew S.; Guleserian, Kristine J.; Forbess, Joseph M.; Zellers, Thomas M.; Vivian Dimas, V.
Abstract : Objective: This study's objective was to evaluate insertion techniques and device fit of the pediatric version of the Impella ventricular assist device in swine which had similar sized carotids and left ventricles (LVs) as children weighing 10–20 kg. Background: Options for minimally invasive circulatory support in children are limited. A modified device based on the current Impella 2.5 platform was created in an effort to provide minimally invasive circulatory support for children. Methods: Animal studies ( n = 10) were performed to determine technical feasibility of device implant via the right common carotid artery (RCCA) in swine with a carotid and LV size similar to children with a BSA < 1 m 2 and weight 10‐20 kg. The RCCA diameter was measured on pre‐implant ultrasound and the LV length was measured at necropsy. The animals were supported for 4 hr and the device explanted. Blood samples and post‐explant necropsy was performed to evaluate for device related complications. Results: All animals underwent successful device insertion. Mean carotid artery diameter by ultrasound was 3.5 ± 0.3 mm. There was no LV or aortic/mitral valve damage with a minimum LV length of 5.4 cm. Conclusions: Minimally invasive circulatory support is needed in small children. Limitations are primarily related to vessel and chamber size. The Impella Pediatric catheter was safely and successfully implanted in carotid arteries similar in size to children weighing 10–20 kg with minimal complications. © 2016 Wiley Periodicals, Inc.